Lichens diversity and index of atmospheric purity of selected sites in Kedah, Malaysia - Rosli, Nur Syuhada; Zulkifly, Shahrizim; Zaharudin, Nur Amalina; Mat Lazim, Nurul Najwa Farihah; Ali, Afni; Go, Rusea (Malaysian Nature Society, 2019)
Lichens are mutualistic association of a fungus and algae that are able to absorb toxic materials from the air making it an excellent bioindicator for air quality assessment. Index of Atmospheric Purity (IAP) is an ecological index that uses lichen frequency to quantify environmental conditions, primarily air pollution. In this study, IAP scores were used to compare the air quality between a forested site, foot hill of Gunung Jerai (GJ) and in an open site, Taman Jubli Perak, Sungai Petani (SP). The lichens were collected at SP and GJ within 5 x 10m sampling site. Twelve trees were chosen at each sampling site and the tree barks were marked with 10 x 50cm sampling grid. Corticolous lichens attached below 100cm from the ground were collected. Standard morphological and chemical tests were conducted lichen species. The air quality of sampling areas, GJ and SP were determined by IAP score, low score indicated high level of pollution. Based on the Quality Level of IAP Table, GJ is classified as moderate polluted (IAP 26.65) and SP (8.3) as very highly polluted. Lichens IAP levels are predominantly affected by lichen habitat disturbance and air pollution. In SP, close proximity of the sampling to the main road traffic may contribute to be cause of the low IAP reading. Meanwhile, in GJ, recreational activities may contribute to the habitat disruption of lichens and low IAP score. As a conclusion, GJ had shown higher IAP score compared to SP due to habitat disturbance and air pollution.